2014
DOI: 10.1101/sqb.2014.79.024844
|View full text |Cite
|
Sign up to set email alerts
|

Representation of Naturalistic Image Structure in the Primate Visual Cortex

Abstract: The perception of complex visual patterns emerges from neuronal activity in a cascade of areas in the primate cerebral cortex. We have probed the early stages of this cascade with “naturalistic” texture stimuli designed to capture key statistical features of natural images. Humans can recognize and classify these synthetic images and are insensitive to distortions that do not alter the local values of these statistics. The responses of neurons in the primary visual cortex, V1, are relatively insensitive to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 49 publications
6
39
0
Order By: Relevance
“…Previous work in macaque (Rust & Dicarlo, 2010) has found that responses in IT differ between intact and scrambled versions of the same image to a greater degree than do the responses in V4 when the Portilla-Simoncelli algorithm is used. A recent report using fMRI in humans (Freeman, Ziemba, Simoncelli, & Movshon, 2013; Movshon & Simoncelli, 2014) has contrasted responses to Portilla-Simoncelli scrambled textures and intact natural textures and found differential responses occurred only at and beyond area V4. Our approach may thus make the resulting SSVEP more selective to the intrinsic structure of orthography and faces than other approaches such as phase scrambling.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in macaque (Rust & Dicarlo, 2010) has found that responses in IT differ between intact and scrambled versions of the same image to a greater degree than do the responses in V4 when the Portilla-Simoncelli algorithm is used. A recent report using fMRI in humans (Freeman, Ziemba, Simoncelli, & Movshon, 2013; Movshon & Simoncelli, 2014) has contrasted responses to Portilla-Simoncelli scrambled textures and intact natural textures and found differential responses occurred only at and beyond area V4. Our approach may thus make the resulting SSVEP more selective to the intrinsic structure of orthography and faces than other approaches such as phase scrambling.…”
Section: Discussionmentioning
confidence: 99%
“…The parametric texture model of Portilla and Simoncelli (Portilla & Simoncelli, 2000;Simoncelli & Portilla, 1998) extended this approach by additionally matching the correlations between channels and other statistics, producing more realistic appearance matches to textures. This model has since had broad impact on the field of human perception and neuroscience: the texture statistic representation may provide a fruitful way to understand the processing in midventral visual areas (Freeman & Simoncelli, 2011;Freeman, Ziemba, Heeger, Simoncelli, & Movshon, 2013;Movshon & Simoncelli, 2014;Okazawa, Tajima, & Komatsu, 2015;Ziemba, Freeman, Movshon, & Simoncelli, 2016), and it has been argued to provide a good approximation of the type of information encoded in the periphery, and thus a model for tasks such as crowding and visual search (Balas, Nakano, & Rosenholtz, 2009;Freeman & Simoncelli, 2011;Keshvari & Rosenholtz, 2016;Rosenholtz, 2011;Rosenholtz, Huang, & Ehinger, 2012;Rosenholtz, Huang, Raj, Balas, & Ilie, 2012)-though other evidence questions the more general adequacy of this representation for explaining crowding and peripheral appearance (Agaoglu & Chung, 2016;Clarke, Herzog, & Francis, 2014;Herzog, Sayim, Chicherov, & Manassi, 2015;Wallis, Bethge, & Wichmann, 2016).…”
Section: Studying Texture Perception With Parametric Texture Modelsmentioning
confidence: 99%
“…The parametric texture model of Portilla and Simoncelli (Portilla & Simoncelli, 2000;Simoncelli & Portilla, 1998) extended this approach by additionally matching the correlations between channels and other statistics, producing more realistic appearance matches to textures. This model has since had broad impact on the field of human perception and neuroscience: the texture statistic representation may provide a fruitful way to understand the processing in mid-ventral visual areas (Freeman & Simoncelli, 2011;Freeman, Ziemba, Heeger, Simon-celli, & Movshon, 2013;Movshon & Simoncelli, 2014;Okazawa, Tajima, & Komatsu, 2015;Ziemba, Freeman, Movshon, & Simoncelli, 2016), and it has been argued to provide a good approximation of the type of information encoded in the periphery, and thus a model for tasks such as crowding and visual search (Balas, Nakano, & Rosenholtz, 2009;Freeman & Simoncelli, 2011;Keshvari & Rosenholtz, 2016;Rosenholtz, 2011;Rosenholtz, Huang, & Ehinger, 2012;Rosenholtz, Huang, Raj, Balas, & Ilie, 2012)-though other evidence questions the more general adequacy of this representation for explaining crowding and peripheral appearance (Agaoglu & Chung, 2016;Clarke, Herzog, & Francis, 2014;Herzog, Sayim, Chicherov, & Manassi, 2015;Wallis, Bethge, & Wichmann, 2016).…”
Section: Studying Texture Perception With Parametric Texture Modelsmentioning
confidence: 99%